Palestinian physicians’ self-reported practice regarding antibiotic use for upper respiratory tract infections in primary healthcare - Maraqa, Bessan; Nazzal, Zaher; Hamshari, Suha; Matani, Nardine; Assi, Yasmeen; Aabed, Mousa; Alameri, Furqan (Frontiers in Medicine, 2023)
Abstract: Background: The main objective of this study was to evaluate the antimicrobial therapy knowledge, attitudes, and practices of primary care physicians in the West Bank and Gaza. Methods: Between January and April of 2021, this cross-sectional survey was conducted. Aa link to the online survey was sent via confidential email lists to 336 primary care physicians who treated patients in Ministry of Health clinics. SPSS software was utilized for data analysis. A The survey questions scoring system was devised in order to evaluated the physicians' practice, knowledge, and attitudes. Our scoring system identified favorable (good) and unfavorable (average and poor) antibiotic practices Independent T-test, the Chi-square test was used to compare the two groups' of physicians’ knowledge, attitudes, and practices with their background characteristics. A multivariate analysis was performed to identify potential confounding variables having significant relationships. Results: Of the 336 distributed questionnaires 316 were completed, with response rate 94%. More than half (54.7%) were males, half (51.6%) were between 30 and 45 years of age, and most were general practitioners (74.1%). The overall favorable knowledge and attitude scores were 125 (39.6 %), and 194 (61.4%), respectively. More than half (58.2%) had good antibiotic prescription practices. Females reported significantly more favorable practices than males, as did family medicine specialists compared with GPs. Finally, knowledge about antibiotic prescriptions had a substantial impact on changing their practices. However, physicians’ attitudes toward antibiotic prescriptions, did not have a significant role in shaping their practices. Conclusions: Overuse of antibiotics is a significant health issue in Palestine and worldwide. Most physicians know that improper antibiotic usage can cause antimicrobial resistance. More than two-thirds avoided needless antimicrobial prescriptions. In practicing antimicrobial stewardship, most prescribed fewer antibiotics and did not prescribe because of patient pressure. Family medicine specialists, female doctors, and those with high knowledge scores regardless of caseload were more likely to have good practices.